Benchmarking the vitality of shrinking rural regions in Finland - Makkonen Teemu; Inkinen Tommi (Elsevier Ltd, 2025)
Depopulation, commonly labelled as shrinkage, of rural areas can lead to a self-reinforcing vicious cycle of decreased regional vitality. However, some regions have been able to adapt to shrinkage and maintain their vitality despite the population loss. Thus, they have been able to “shrink smart”. While there is a growing interest in this topic and particularly in the policies facilitating adaptation to depopulation, there is no commonly agreed measure to depict smart shrinkage. This paper aims at devising novel metrics for benchmarking the (full) development potential of depopulating rural areas as a way forward in the study of smart shrinkage. The proposed metrics, tested with data from Finnish municipalities, provides a good overview of which regions are doing well in terms of their economy and community vitality despite shrinkage, and helps in the selection of interesting case regions for further in-depth analysis.